Traumatic Bony Lesion Turned Out to be Rare Radial Metastasis of Follicular Thyroid Carcinoma-A Case Report (Bangladesh Journal of Nuclear Medicine, 2025)
Follicular thyroid carcinoma (FTC) is the second most prevalent thyroid cancer and usually causes blood borne metastases. However, distant metastases to bone are common in differentiated thyroid cancer, solitary bone metastasis in appendicular skeleton is a rare condition. We report an unusual case of solitary bone metastasis to radius in 52 years, male patient presenting as post-traumatic, non-tender, firm, fixed swelling at left forearm for six months.99mTc-methylene diphosphonate (99mTc-MDP) bone scintigraphy [planar and single photon emission CT (SPECT)] was the radiological modality of choice for the detection of the solitary bone metastasis in this patient with follicular thyroid carcinoma (FTC).In addition to bone scintigraphy, 99mTc thyroid scan had added the role of nuclear medicine study to detect both primary site and secondary site of metastasis.Bangladesh J. Nuclear Med. 27(2): 279-283, 2024